Інтегральна оцінка ресурсної ефективності промисловості регіонів України - Созанський, Л.Й. (Економіка промисловості, 2017)
Здійснено інтегральну оцінку ресурсної ефективності промисловості регіонів України, сформульовано аналітичні висновки, міжрегіональні порівняння та пропозиції щодо підвищення ресурсної ефективності промисловості України. Осуществлена интегральная оценка ресурсной эффективности промышленности регионов Украины, сформулированы аналитические выводы, межрегиональные сравнения и предложения по повышению ресурсной эффективности промышленности Украины. Resource efficiency of industry is characterized by two key indicators: capital productivity and labor productivity. The first one reflects the management efficiency of fixed assets,and the second one - human resources. Capital productivity of Ukraine’s regions industry is calculated as the ratio of volume of industrial products sold to the value of fixed assets and labor productivity - as the ratio of volume of industrial products sold to the average number of workers employed in industry.By integrating of the indices of the capital productivity and labor productivity the industry resource efficiency indices have been calculated, and on its basis the grouping of Ukraine’s regions has been made. Under certain graduation in 2015 the half of Ukraine’s regions (12) was characterized by the average resource efficiency of industry. A high level of resource efficiency was characteristic of industry of three areas (Poltava, Cherkassy, and Sumy). Low level of resource efficiency was characteristic of industrial sectors of the rest 9 regions.The analysis of the capital productivity and labor productivity revealed that in 2015 there was a decrease of the average number of industry workers in all regions of Ukraine except Rivne, and in six regions - decrease of the fixed assets. The proposed directions of increasing the resource efficiency of Ukraine’s regions are creation and organization of activities of educational, scientific and production centers of industry and regional areas, public-private enterprises in manufacturing and improving the functioning of state procurement.